From the Centre/Periphery Dichotomy to Implicated Readers: Reading Tash Aw’s We, The Survivors - Sanghamitra Dalal (Asiatic: IIUM Journal of English Language and Literature, 2022)
In this article, I shall examine the problematic disposition of voice and agency as described in the London-based Malaysian author Tash Aw’s latest novel We, The Survivors (2019). The novel is constructed in the form of an oral testimony, narrated by the protagonist, an impoverished third-generation Chinese- Malaysian, Ah Hock, who is convicted for a culpable homicide of a migrant worker. It is framed by the non-intrusive presence of a Malaysian scholar, Su- Min, who interviews him as part of her field research project, and publishes his life-story in a book form. However, in the course of my discussion, I shall contend that Aw not only problematises the issue of voice appropriation in storytelling, but also questions the deeply residing chasms lying inherent in the existing societal structures. Drawing from Michael Rothberg’s proposition of the implicated subject and Hannah Arendt’s views on collective responsibility, I shall argue that Tash Aw’s “we” attempts to dismantle the stereotypical boundaries of centre and periphery. Through its specific focus on the predicament of the immigrants in Malaysia, the novel eventually strives to create a network of implicated subjects which includes not only the author and the readers, but also everyone else in society.